2012
DOI: 10.1155/2012/769896
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the PhytomedicineEchinacea purpurea(Purple Coneflower) in Infectious Diseases

Abstract: Extracts of Echinacea purpurea (EP, purple coneflower) have been used traditionally in North America for the treatment of various types of infections and wounds, and they have become very popular herbal medicines globally. Recent studies have revealed that certain standardized preparations contain potent and selective antiviral and antimicrobial activities. In addition, they display multiple immune-modulatory activities, comprising stimulation of certain immune functions such as phagocytic activity of macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 126 publications
(189 reference statements)
0
92
1
6
Order By: Relevance
“…Chamomile extract has also been shown to possess anti-inflammatory properties (11). Echinacea is claimed to stimulate the immune response and to activate leukocytes (12). Reports attribute analgesic, anti-inflammatory, and antimicrobial properties to peppermint oil (13).…”
mentioning
confidence: 99%
“…Chamomile extract has also been shown to possess anti-inflammatory properties (11). Echinacea is claimed to stimulate the immune response and to activate leukocytes (12). Reports attribute analgesic, anti-inflammatory, and antimicrobial properties to peppermint oil (13).…”
mentioning
confidence: 99%
“…This plant is well known as a medicinal plant for its effects in strengthening the immune system and for its antiviral activity. 11,12 In a previous study, these species responded differently when irradiated with different light sources, and particularly with Fluora and LEDs. 13 On this basis, this research is aimed at investigating the effects of UV-C light the photosynthetic and physiological responses of these two rustic plants.…”
Section: Introductionmentioning
confidence: 87%
“…Polysaccharide constituent of the plant Echinacea purpurea were found to enhance phagocyte activity and to inhibit growth of Candida albicans and Listeria monocytogenes in mice (Roesler et al, 1991). Moreover, certain standardized preparations of Echinacea purpurea were proven to have potent antimicrobial and antiviral activity in humans (Hudson, 2012). Barbour et al (2000) reported that a dose of 0.147% supplementation of Echinacea pupurea roots to broiler feeds induced immunopotentiation, reduced immunosuppression caused by Infectious Bursal Disease (IBD), and lowered infectivity by Salmonella Enteritidis.…”
Section: A Review Of Approaches Targeting the Replacement Of Coccidiomentioning
confidence: 99%